In vivo proximity proteomics of nascent synapses reveals a novel regulator of cytoskeleton-mediated synaptic maturation - Erin F. Spence (Nature Portfolio, 2019)
The internal molecular mechanisms that underlie excitatory synaptogenesis remain poorly characterized. This study utilizes a chemogenetic approach, in vivo biotin identification (iBioID), to discover previously uncharacterized proteins at nascent synapses. CARMIL3 is identified as a cytoskeletal protein that facilitates spine maturation and AMPAR recruitment.